A strategy to prioritize emerging drugs of abuse for analysis: Abuse liability testing using intracranial self-stimulation (ICSS) in rats and validation with α-pyrrolidinohexanophenone (α-PHP). (2021) - Baird, Tyson R.; Davies, Rachel A.; Glennon, Richard A.; Peace, Michelle R.; Negus, S. Stevens
Abstract: Novel psychoactive substances (NPS) threaten public health and safety while also straining the limited resources of forensic laboratories. To efficiently allocate the finite resources available, we propose a new strategy for prioritizing NPS with abuse liability testing using a preclinical behavioral procedure in rats known as intracranial self-stimulation (ICSS). To validate this assay, the recently-scheduled synthetic cathinone α-PHP was compared to cocaine, a mechanistically similar drug of abuse, as a positive control and saline as a negative control. Male Sprague-Dawley rats (n=6) were implanted with electrodes targeting the medial forebrain bundle and trained to respond by lever-press for electrical brain stimulation. The rats were tested with doses of 0.32, 1.0, and 3.2 mg/kg α-PHP as well as 10 mg/kg of cocaine and saline administered by intraperitoneal injection. Neither saline nor 0.32 mg/kg α-PHP altered ICSS response rates compared to baseline levels of responding; however, doses of 1.0 and 3.2 mg/kg α-PHP and 10 mg/kg cocaine facilitated ICSS responding. This ICSS profile suggests that α-PHP has high abuse potential, with a rapid onset of effects and a long duration of action, and supports the decision to schedule this compound. This study demonstrates the ability of ICSS to distinguish between compounds of low and high potential for abuse. A strategy is proposed here to screen NPS using ICSS and classify emerging drugs into four priority categories for further analysis.